Optimal DG Location and Sizing for Minimum Active Power Loss in Radial Distribution System using Firefly Algorithm - souhaib remha (International Journal of Energetica)
In this paper, a novel optimization algorithm is presented for optimal location and sizing of Distributed Generation (DG) units on distribution systems. For this purpose, a recently based meta-heuristic called Firefly Algorithm (FA) has been employed to minimize the total active power losses. The results show a considerable improved in voltage profiles of all the buses and enhance the voltage stability index. The investigations were tested on IEEE 33 bus radial distribution system. Simulation results demonstrate the effectiveness of firefly algorithm. Comparison with another method is also given.